Az e-HRM megjelenése, avagy a humán erőforrás menedzsment hetedik szakasza - Gulyás László (Közép-európai Monográfiák, 2018)
According to the international literature of HRM the development of human resource management consists of six period. They are the following: 1. period: the social reformer 2. period: welfare officer 3. period: humane bureaucrat 4. period: the consensus negotiator 5. period: organization man 6. period: manpower analyst. First part of our essay shows the features of these six parts. The next part of our essay is beginning with this question: Where is human resource management, the seventh period has already begun? In the second part of our essay we investigate this question. Our opinion is: The seventh period started and it called e-HRM. According to this opinion we are examining the development of e-HRM.